Cross-validation of the safe supplement screener (S3) predicting consistent third-party-tested nutritional supplement use in NCAA Division I athletes - Schott, Kinta D.; Bhalla, Avaani; Armstrong, Emma; Seltzer, Ryan G. N.; Wardenaar, Floris C. (Frontiers in Nutrition, 2025)
IntroductionThis cross-sectional study aimed to cross-validate an earlier developed algorithm-based screener and explore additional potential predictors for whether athletes will use third-party-tested (TPT) supplements.MethodsTo justify the initial model behind the supplement safety screener (S3) algorithm which predicts whether athletes will use TPT supplements, a cross-validation was performed using this independent dataset based on responses of a large group of collegiate NCAA DI athletes. Additionally, explorative modeling using stepwise logistic regression was used to identify new predictors for TPT supplement use to create and evaluate a new model for future use.ResultsThe S3 algorithm was applied to the responses from n = 662 athletes using supplements (age: 20 ± 1.5 years, 50% female, from >24 sports) confirming that the algorithm identifies consistent and inconsistent TPT users (χ2 (1) = 15.95, p < 0.001), with a moderate area under the curve (AUC, 0.67) and a moderate specificity (68%), but low sensitivity (51%). Explorative modeling identified two new variables: TPT logo recognition, and having at least one name, image, likeness (NIL) deal that may help to predict TPT supplement use.DiscussionStrong relationships between risk groupings and product use outcomes toward TPT supplement use were identified for the athletes screened. The S3 screener showed high sensitivity for identifying student-athletes inconsistently using TPT supplements, but a low specificity, lacking the ability to place less risky athletes into low-risk quadrants. The exploratory modeling, identifying TPT logo recognition and having a NIL deal, further strengthens our knowledge on predictors for consistent TPT supplement use.